Evolution of stretching lineations in granulite-hosted ductile shear zones, Eastern Ghats Province, India: Role of temperature, strain rate and pre-existing stretching lineations. (September 2020) - Bose, Subham; Gupta, Saibal
Abstract: Shear zone kinematics are interpreted from sections (X-Z) parallel to the stretching lineation (X-direction) and perpendicular to the mylonitic foliation (X–Y). The stretching lineation is a product of finite strain, defined by minerals or mineral aggregates that deform plastically. In quartzofeldspathic rocks deformed below 600 °C, rheological contrasts between quartz and feldspar are amplified, and the mesoscopic stretching lineation in the shears may be indistinct in outcrop as quartz ribbons anastomose around relatively competent feldspar clasts. In high strain-rate zones, rheological contrasts between these minerals are reduced and a stretching lineation suitable for kinematic interpretation develops . In late amphibolite and greenschist facies shear zones transecting pre-lineated quartzofeldspathic granulites of the Eastern Ghats Province, India, the stretching lineation represents the resultant of pre-existing stretch and superposed increments of later shearing. Until the stretch accumulated in the X-direction of the later deformation exceeds the earlier finite stretch, the pre-existing stretching lineation progressively rotates towards the later X-direction with decreasing aspect ratio. These intermediate lineation orientations, have no kinematic relevance to either earlier or later deformations. This example highlights the importance of temperature, strain rate and orientation of pre-existing stretching lineations in the appearance and kinematic interpretation of, stretching lineations in ductile shear zones. Highlights: Stretching lineations in shear zone are defined by minerals that deform plastically. Rheological contrast between minerals amplify in low to moderate strain rate zones. Weak minerals wrapping rigid clasts reduce lineation visibility in low strain zones. Lower rheological contrasts in high strain rate zones enhances lineation visibility. Stretching lineations in low strain zones may lead to erroneous kinematic analyses.